By the method of determining the path of friction in friction units to the complex plane-parallel motion / V.I. Kubich, A.O. Shchadniev, L.I. Ivschenko // Problems of Tribology. – 2012. – № 1. – Р. 45-51. - Кубич, В.И.; Щаднев, А.О.; Ивщенко, Л.И. (Problems of Tribology, 2014)
The approaches to the graphical modeling of complex movementpatterns with plane-parallel relative motion, which allowed to determine the type of mathematical calculation based on the parameters of the sliding path testing. For information about the trajectory of a sliding distance of the samples at their plane-parallel motion and its mathematical description of the earlier authors were not known to have been obtained and submitted them for the first time.